Formulation of an alternative tasting scheme for the sensory evaluation of beer - Schönberger, Christina; Krottenthaler, Martin; Back, Werner (BrewingScience, 2004)
In terms of sensory evaluation beer often suffers compared to wine since consumers often refuse to concede a sophisticated sensory evaluation for a beer as necessary. In this research a tasting scheme was developed emanating from the "trueness-of-type" scheme, which allows a sensory evaluation not only of the characteristic volatile flavours of beer but also of taste qualities in addition to the main off-flavours. The interpretation may be done in two different ways, in the form of visual comparisons, or in the form of score relations. It was shown that this scheme settles statistical claims in terms of reproducibility. Using this scheme in addition to the widespread DLG-scheme as an instrument for internal quality management holds the possibility to get substantial sensory information of the beer sample.